An Analytical Field Study to Prepare a Rubble Map of the City of Aleppo as a Prelude to the Reconstruction Stage (Journal of Hama University, 2019)
The rubble in the city of Aleppo is very important case and the estimated amount of rubble is of interest to decision-makers. Therefore, a field study was conducted to determine initial rates of damage and definition the components and quantities of building rubble in the city of Aleppo in order to determine the possibility of a real industry for the recycling of rubble and debris. Samples were taken from a large number of places in order to determine the proportions of the different materials forming the rubble like concrete, block and stone. These materials can become after cracking and grinding recyclable material, metal materials make up the bulk of iron and different solid waste (textile, plastic, glass, etc.). After collecting the theoretical and practical data, making comparisons and making some corrections and calibrations, a map of rubble that could be used in the reconstruction phase was charted.